2007
DOI: 10.1002/jcp.21024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of fluid shear stress on endothelial cell proliferation and survival

Abstract: We attempted to clarify the effect of different types of shear stress on endothelial cell (EC) proliferation and survival. Bovine aortic ECs were subjected to either steady laminar, 1 Hz pulsatile, or 1 Hz to and fro shear at 14 dyne/cm(2). % of BrdU positive EC was 14.3 +/- 1.6% in steady, 21.5 +/- 3.2% in pulsatile, and 11.4 +/- 2.4% in to and fro after 4 h, respectively (P < 0.05). Pulsatile shear compared with static control. Rapamycin reduced BrdU incorporation in all shear regimens (P < 0.001). However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 58 publications
8
53
0
Order By: Relevance
“…Likewise, we showed that bovine aortic ECs exposed to pulsatile flow frequencies of 0.5 and 1.0 Hz, but not 1.5 Hz, exhibited elongated morphologies and oriented with the direction of flow [22]. Our laboratory also demonstrated that 1 Hz but not 0.1, 0.5, or 1.5 Hz was optimal for bovine aortic ECs proliferation when exposed to PFF [8]. Interestingly, frequency had no effect on proliferation of bovine aortic ECs exposed to TFF [8].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Likewise, we showed that bovine aortic ECs exposed to pulsatile flow frequencies of 0.5 and 1.0 Hz, but not 1.5 Hz, exhibited elongated morphologies and oriented with the direction of flow [22]. Our laboratory also demonstrated that 1 Hz but not 0.1, 0.5, or 1.5 Hz was optimal for bovine aortic ECs proliferation when exposed to PFF [8]. Interestingly, frequency had no effect on proliferation of bovine aortic ECs exposed to TFF [8].…”
Section: Discussionsupporting
confidence: 58%
“…Our laboratory also demonstrated that 1 Hz but not 0.1, 0.5, or 1.5 Hz was optimal for bovine aortic ECs proliferation when exposed to PFF [8]. Interestingly, frequency had no effect on proliferation of bovine aortic ECs exposed to TFF [8]. Other investigators have also reported that anti-inflammatory responses of porcine aortic ECs exposed to 1 Hz forward flow are reversed at 2 Hz [23].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In particular, mouse models are extremely useful, as several genetic mutations that influence arterial development and behavior have been described. 32,33 Ultimately, wall shear stress is the result of blood flow against the arterial wall, and has been shown to influence endothelial 9,12 and smooth muscle cell behavior. 5,11 Previous investigators have used computational fluid dynamics to estimate wall shear stress in blood vessels using MRI, 34 and this technique could be combined with coil-assisted imaging to allow calculation of wall shear stress in small animal models.…”
Section: Future Directionsmentioning
confidence: 99%
“…1,5,6 Often cell types are isolated and exposed to a single type of flow in an in vitro model such as laminar, to-and-fro, orbital or more complicated patterns. These in vitro studies have led to the identification of several molecular mediators that respond to different flow patterns, [7][8][9][10][11] and recently a shear stress receptor for endothelial cells has been identified. 12 One limitation of these models is that vascular disease is a complex process, involving multiple cell types and interactions between cells and molecular mediators.…”
Section: Introductionmentioning
confidence: 99%